Differentiated Thyroid Cancer: Indications and Extent of Central Neck Dissection—Our Experience. (26th September 2013) - Calò, Pietro Giorgio; Medas, Fabio; Pisano, Giuseppe; Boi, Francesco; Baghino, Germana; Mariotti, Stefano; Nicolosi, Angelo
Abstract : The aim of this retrospective study was to determine the rate of metastases in the central neck compartment and examine the morbidity and rate of recurrence in patients with differentiated thyroid cancer treated with or without a central neck dissection. Two hundred and fifteen patients undergoing total thyroidectomy with preoperative diagnosis of differentiated thyroid cancer, in the absence of suspicious nodes, were divided in two groups: those who underwent a thyroidectomy only (group A;n = 169 ) and those who also received a central neck dissection (group B;n = 46 ). Five cases (2.32%) of nodal recurrence were observed: 3 in group A and 2 in group B. Tumor histology was associated with a risk of recurrence: Hürthle cell-variant and tall cell-variant carcinomas were associated with a high risk of recurrence. Multifocality and extrathyroidal invasion also presented a higher risk, while smaller tumors were at lower risk. The results of this study suggest that prophylactic central neck dissection should be reserved for high-risk patients only. A wider use of immunocytochemical and genetic markers to improve preoperative diagnosis and the development of methods for the intraoperative identification of metastatic lymph nodes will be useful in the future for the improved selection of patients for central neck dissections.